Relation between 25-hydroxy vitamin D and diabetic retinopathy in Egyptian patients with type 2 diabetes mellitus - Mervat E. Elwakeel; Fatma M. El-Senosy; Nesma S. Mohammed; Heba M. Abdelrahman; Eman E. Ebrihem (Journal of the Arab Society for Medical Research)
Background/aim Diabetic retinopathy (DR) is one of the leading causes of blindness in people whose ages range from 20 to 64 worldwide. This study aims to evaluate the association of serum 25-hydroxy (OH) vitamin D deficiency and DR in type 2 diabetes mellitus (T2DM) patients. Patients and methods A cross-sectional study was conducted on 90 Egyptian patients with T2DM. Patients were divided into two groups: group I included 44 patients without retinopathy and group II included 46 with retinopathy. Group II was subdivided into two subgroups, group IIa, which included 26 nonproliferative DR patients and group IIb, which included 20 proliferative DR patients. Anthropometric data and laboratory investigations, including fasting and the postprandial blood sugar, glycated hemoglobin, lipid profiles, and serum vitamin D level. A fundus examination was also performed. Results The present results exhibited a significant decrease (P<0.05) of serum vitamin D (25-OH-vitamin D) in patients with T2DM and this deficiency is more in group II in comparison to group I and in a patient with proliferative DR (group IIb) compared to nonproliferative DR (group IIa). Also, there was a downward trend in serum vitamin D with the severity of DR. Also 25-OH-vitamin D level was inversely correlated with fasting, postprandial blood sugar, and glycated hemoglobin. A cut-off value for serum vitamin D levels of less than or equal to 12.03 ng/ml served as a sensitive indicator for DR. Conclusion 25-OH-vitamin D deficiency is highly prevalent in Egyptian patients with T2DM and this deficiency is highly associated with the presence and severity of DR.